Floristics and structure of the tree component in a Seasonal Forest remnant, Chiapetta, Rio Grande do Sul State, Brazil - Benvenuti-Ferreira, Glaci; Coelho, Geraldo Ceni (Revista Brasileira de Biociências, 2009)
In a patchy landscape, the forest remnants are important to the conservation of wild species. A phytossociological study of tree component in a remnant of Seasonal Semideciduous Forest site namely Mato do Silva (27º55’26’’ S, 53º53’15’’ W, 290 ha) was accomplished aiming to obtain data of plant community structure and its conservation status, comparing with other Seasonal Forest sites. A sample of 508 trees (DBH ≥ 5.0 cm), belonging to 31 families and 63 species, was attained through the point-quarter procedure. The outstanding families in terms of richness were Fabaceae (eleven species), Myrtaceae, Rutaceae, Sapindaceae, Lauraceae and Euphorbiaceae (four species each one). The species with the highest importance value were Cordia americana (L.) Gottschling & J.E.Mill. (35.5), Diatenopteryx sorbifolia Radlk. (32.3) and Prunus myrtifolia (L.) Urban (19.1). The dead trees presented a relative density of 4.9%. The majority of the species (65%) and individuals (55%) were zoochoric. Otherwise, the anemochory presented higher relative coverage (55%). The species with the higher IV values were mainly early secondary and anemochoric. The Shannon index of diversity (H’) was 3.68 and the Pielou’s evenness index (J’) was 0.89. These values are among the highest values observed in Seasonal Forests of South Brazil. The floristic inventory counted 117 tree species.